Equatorial Non-muscle Myosin II and Plastin Cooperate to Align and Compact F-actin Bundles in the Cytokinetic Ring - Leite, Joana; Chan, Fung-Yi; Osório, Daniel S.; Saramago, Joana; Sobral, Ana F.; Silva, Ana M.; Gassmann, Reto; Carvalho, Ana X. (Frontiers in Cell and Developmental Biology, 2020)
Cytokinesis is the last step of cell division that physically partitions the mother cell into two daughter cells and requires the assembly and constriction of a contractile ring, a circumferential array of filamentous actin (F-actin), non-muscle myosin II motors (myosin), and actin-binding proteins that forms at the cell equator. Cytokinesis is accompanied by long-range cortical flows from regions of relaxation towards regions of compression. In the C. elegans one-cell embryo, it has been suggested that anterior-directed cortical flows are the main driver of contractile ring assembly. Here, we use embryos co-expressing motor-dead and wild-type myosin to show that cortical flows can be severely reduced without major effects on contractile ring assembly and timely completion of cytokinesis. Fluorescence recovery after photobleaching in the ingressing furrow reveals that myosin recruitment kinetics are also unaffected by the absence of cortical flows. We find that myosin cooperates with the F-actin crosslinker plastin to align and compact F-actin bundles at the cell equator, and that this cross-talk is essential for cytokinesis. Our results thus argue against the idea that cortical flows are a major determinant of contractile ring assembly. We propose that contractile ring assembly requires localized concerted action of motor-competent myosin and plastin at the cell equator.